The Relationship between Age and Anxiety with the Time Interval of the Second Stage of Labor at RSIA Qurrata A'yun in 2022 - Retno Aprilia Sandra; Edi Sukamto; Siti Raihanah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Obstructed/long labor is one of the causes of bleeding which results in labor death. One of the causes is the psychology of the mother in labor due to weak uterine contractions. The aim of this study was to examine the relationship between age and maternal anxiety with the second stage of labour. This study used a cross-sectional study with a population of 30 mothers giving birth at RSIA Qurarata A'yun during June-July 2022. The sampling technique used is accidental sampling. The data processing used is chi-square. Maternal age resulted in a Pvalue of 0.042 (< α 0.05) with an OR (95% CI) of 0.4x and anxiety produced a Pvalue of 0.188 (> α 0.05). Mothers should plan pregnancies at a vulnerable age that has a low risk and the importance of managing pain and anxiety during childbirth.